![\large\underline{\sf{Solution-}}](https://tex.z-dn.net/?f=%5Clarge%5Cunderline%7B%5Csf%7BSolution-%7D%7D)
We have to <u>evaluate</u> the given <u>expression</u>.
![\rm = \sqrt{ \dfrac{1 - \sin(x) }{1 + \sin(x) } }](https://tex.z-dn.net/?f=%20%5Crm%20%3D%20%20%5Csqrt%7B%20%5Cdfrac%7B1%20-%20%20%5Csin%28x%29%20%7D%7B1%20%2B%20%20%5Csin%28x%29%20%7D%20%7D%20)
If we multiple both numerator and denominator by 1 - sin(x), then the value remains same. Let's do that.
![\rm = \sqrt{ \dfrac{[1 - \sin(x)][1 - \sin(x) ]}{[1 + \sin(x)][1 - \sin(x) ]} }](https://tex.z-dn.net/?f=%20%5Crm%20%3D%20%20%5Csqrt%7B%20%5Cdfrac%7B%5B1%20-%20%20%5Csin%28x%29%5D%5B1%20-%20%20%5Csin%28x%29%20%5D%7D%7B%5B1%20%2B%20%20%5Csin%28x%29%5D%5B1%20-%20%20%20%5Csin%28x%29%20%5D%7D%20%7D%20)
![\rm = \sqrt{ \dfrac{[1 - \sin(x)]^{2}}{1- \sin^{2} (x) } }](https://tex.z-dn.net/?f=%20%5Crm%20%3D%20%20%5Csqrt%7B%20%5Cdfrac%7B%5B1%20-%20%20%5Csin%28x%29%5D%5E%7B2%7D%7D%7B1-%20%20%20%5Csin%5E%7B2%7D%20%28x%29%20%7D%20%7D%20)
<u>We know that:</u>
![\rm \longmapsto { \sin}^{2}(x) + \cos^{2}(x) = 1](https://tex.z-dn.net/?f=%20%5Crm%20%5Clongmapsto%20%7B%20%5Csin%7D%5E%7B2%7D%28x%29%20%2B%20%20%5Ccos%5E%7B2%7D%28x%29%20%20%3D%201)
![\rm \longmapsto \cos^{2}(x) = 1 - { \sin}^{2}(x)](https://tex.z-dn.net/?f=%20%5Crm%20%5Clongmapsto%20%20%5Ccos%5E%7B2%7D%28x%29%20%20%3D%201%20-%20%20%7B%20%5Csin%7D%5E%7B2%7D%28x%29)
Therefore, <u>the expression becomes:</u>
![\rm = \sqrt{ \dfrac{[1 - \sin(x)]^{2}}{\cos^{2} (x)}}](https://tex.z-dn.net/?f=%20%5Crm%20%3D%20%20%5Csqrt%7B%20%5Cdfrac%7B%5B1%20-%20%20%5Csin%28x%29%5D%5E%7B2%7D%7D%7B%5Ccos%5E%7B2%7D%20%28x%29%7D%7D%20)
![\rm = \dfrac{1 - \sin(x)}{\cos(x)}](https://tex.z-dn.net/?f=%20%5Crm%20%3D%20%20%5Cdfrac%7B1%20-%20%20%5Csin%28x%29%7D%7B%5Ccos%28x%29%7D)
![\rm = \dfrac{1}{\cos(x)} - \dfrac{ \sin(x) }{ \cos(x) }](https://tex.z-dn.net/?f=%20%5Crm%20%3D%20%20%5Cdfrac%7B1%7D%7B%5Ccos%28x%29%7D%20-%20%20%5Cdfrac%7B%20%5Csin%28x%29%20%7D%7B%20%5Ccos%28x%29%20%7D%20)
![\rm = \sec(x) - \tan(x)](https://tex.z-dn.net/?f=%20%5Crm%20%3D%20%20%5Csec%28x%29%20-%20%20%5Ctan%28x%29%20)
The rule for multiplying similar bases with exponents:
(a^b)(a^c)=a^(b+c)
In this case we have:
(5^-2)(5^-1)
5^(-2-1)
5^(-3)
The rule for negative exponents:
a^(-b)=1/(a^b)
So in this case:
5^(-3) is equal to
1/(5^3)
1/125
Simply cross multiply and simplify to get a = 11
Hope this helped!! xx
B 6.44 because 6.4 is equal to 6.40 and in between 6.40 and 6.60 there is 6.44.